Unintended pregnancy and contraception use among African women living with HIV: Baseline analysis of the multi-country US PEPFAR PROMOTE cohort - Aizire, Jim; Yende-Zuma, Nonhlanhla; Hanley, Sherika; Nematadzira, Teacler; Nyati, Mandisa M; Dadabhai, Sufia; Chinula, Lameck; Nakaye, Catherine; Fowler, Mary Glenn; Taha, Taha (Public Library of Science, 2024)
About 90% of unintended pregnancies are attributed to non-use of effective contraception-tubal ligation, or reversible effective contraception (REC) including injectables, oral pills, intra-uterine contraceptive device (IUCD), and implant. We assessed the prevalence of unintended pregnancy and factors associated with using RECs, and Long-Acting-Reversible-Contraceptives (LARCs)-implants and IUCDs, among women living with HIV (WLHIV) receiving antiretroviral therapy (ART). We conducted cross-sectional analyses of the US-PEPFAR PROMOTE study WLHIV on ART at enrollment. Separate outcome (REC and LARC) modified-Poisson regression models were used to estimate prevalence risk ratio (PRR) and corresponding 95% confidence interval (CI). Of 1,987 enrolled WLHIV, 990 (49.8%) reported their last/current pregnancy was unintended; 1,027/1,254 (81.9%) non-pregnant women with a potential to become pregnant reported current use of effective contraception including 215/1,254 (17.1%) LARC users. Compared to Zimbabwe, REC rates were similar in South Africa, aPRR = 0.97 (95% CI: 0.90-1.04), p = 0.355, lower in Malawi, aPRR = 0.84 (95% CI: 0.78-0.91), p<0.001, and Uganda, 0.82 (95% CI: 0.73-0.91), p<0.001. Additionally, REC use was independently associated with education attained, primary versus higher education, aPRR = 1.10 (95% CI: 1.02-1.18), p = 0.013; marriage/stable union, aPRR = 1.10 (95% CI: 1.01-1.21), p = 0.039; no desire for another child, PRR = 1.10 (95% CI: 1.02-1.16), p = 0.016; infrequent sex (none in the last 3 months), aPRR = 1.24 (95% CI: 1.15-1.33), p<0001; and controlled HIV load ([less than or equal to] 1000 copies/ml), PRR = 1.10 (95% CI: 1.02-1.19), p = 0.014. LARC use was independently associated with country (Zimbabwe ref: South Africa, PRR = 0.39 (95% CI: 0.26-0.57), p<0.001; Uganda, PRR = 0.65 (95% CI: 0.42-1.01), p = 0.054; and Malawi, aPRR = 0.87 (95% CI: 0.64-1.19), p = 0.386; HIV load ([less than or equal to] 1000 copies/ml copies/ml), aPRR=1.73 (95% CI: 1.26-2.37), p<0.001; and formal/self-employment, aPRR = 1.37 (95% CI: 1.02-1.91), p = 0.027. Unintended pregnancy was common while use of effective contraception methods particularly LARCs was low among these African WLHIV. HIV viral load, education, sexual-activity, fertility desires, and economic independence are pertinent individual-level factors integral to the multi-level barriers to utilization of effective contraception among African WLHIV. National programs should prioritize strategies for effective integration of HIV and reproductive health care in the respective African countries.
Keywords: Pregnancy; Female contraception; HIV ; Contraceptives ; Assisted reproductive technology ; South Africa ; Uganda; Medical implants